Small bowel malignant tumor: a diagnostic dilemma, a case report and literature review - Makhdoomi, Mahmood A.; Almotlaq, Abdulaziz; Tawfiq, Nader A. (International Surgery Journal, 2020)
A 47 years old Saudi male was admitted to king Khalid hospital with complaints of constipation and abdominal distension. Abdominal examination showed as a case of intestinal obstruction. He was fully evaluated and was treated first conservatively, until all investigative study confirmed as huge small bowel dilatation (mainly jejunum). Exploratory laparotomy confirmed small bowel tumor and on histology an adenocarcinoma. The introduction, history and research paper will also be discussed in this report.